Feminist Spirituality as Lived Religion: How UK Feminists Forge Religio-spiritual Lives. (February 2015) - Aune, Kristin
How do feminists in the United Kingdom view spirituality and religion? What are their religious and spiritual attitudes, beliefs, and practices? What role do spirituality and religion play in feminists' lives? This article presents findings from an interview-based study of 30 feminists in England, Scotland, and Wales. It identifies three characteristics of feminists' approaches to religion and spirituality: They are de-churched, are relational, and emphasize practice. These features warrant a new approach to feminists' relationships with religion and spirituality. Rather than, as others have done, equating feminism with secularism, secularization, or alternative spiritualities, the article reveals the complex ways feminists forge religio-spiritual lives. The interview data demonstrate that it is unwise to see "spirituality" and "religion" as analytically distinct. Instead, drawing on the growing field of scholarship on "lived religion, " the article proposes conceptualizing feminist spirituality as lived religion.